A Case of Hypophosphatasia that Was Overlooked for a Long Time in a Patient with a Novel Duplication Mutation in ALPL - Kawashima, Hisashi; Sasame, Atsuko; Ogaki, Yoko; Nakayama, Takayuki; Okuno, Hironobu (Archives of Clinical and Medical Case Reports, 2024)
We report a case of hypophosphatasia that was overlooked for a long time in a patient with a novel mutation in the ALPL gene, coding for tissue-nonspecific alkaline phosphatase. A 49-year-old man who had been experiencing frequent fractures since childhood showed a low serum alkaline phosphatase level in a routine health checkup. His bone mineral density was also low. Analysis of his ALPL gene showed that he was heterozygous for c.1171dup (p.Arg391ProfsTer14), which was a frameshift variant. From these results, he was diagnosed as having hypophosphatasia caused by a novel mutation.